The end of policing - Vitale, Alex S. (Verso, 2021)
Preface to the 2021 edition --The limits of police reform --The police are not here to protect you --The School-to-Prison pipeline --"We called for help, and they killed my son" --Criminalizing homelessness --The failures of policing sex work --The war on drugs --Gang suppression --Border policing --Political policing --Conclusion --Afterword to the 2021 edition.